2012
DOI: 10.1016/j.puhe.2012.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer mortality in Spain: Has it really declined for all age groups?

Abstract: Introduction: Incidence in Spain due to breast cancer has increased over the last few years, nevertheless mortality has decreased, especially since 1992. Despite this general decrease in mortality, the intensity has been different in all age groups. The main objective of this paper is to fit the mortality due to breast cancer for different age groups in Spain during Results: We found an evident decreasing trend during the last few years of the fit (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
2
10
0
2
Order By: Relevance
“…The Eurocare-4 study, which analyzed survival in cancer patients diagnosed from 1995 to 1999, showed that 5-year RS in France for patients with BC was 83%. These results are consistent with reports in the literature, 29,30 which show a trend towards improved BC survival over the same period. 26 According to these studies, RS was longer in our population than in the whole population of BC patients in France.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The Eurocare-4 study, which analyzed survival in cancer patients diagnosed from 1995 to 1999, showed that 5-year RS in France for patients with BC was 83%. These results are consistent with reports in the literature, 29,30 which show a trend towards improved BC survival over the same period. 26 According to these studies, RS was longer in our population than in the whole population of BC patients in France.…”
Section: Discussionsupporting
confidence: 93%
“…28 Furthermore, the present results showed a trend towards a decrease in mortality as a result of breast cancer over time. These results are consistent with reports in the literature, 29,30 which show a trend towards improved BC survival over the same period.…”
Section: Discussionsupporting
confidence: 93%
“…3 A decrease in mortality from breast cancer was also observed in young and middle-aged women in Spain from 1993 to 2007, although it remained stable for older women. 22 In Portugal, there was a decrease in mortality for this disease at 2% per year between 1992 and 2002. 23 Sin- ce a peak in the late 1980s, mortality rates from breast cancer have also reduced by almost 40% in the UK, and in the last 10 years the mortality rates due to breast cancer have fallen by almost 20%.…”
Section: Discussionmentioning
confidence: 99%
“…In Spain the trend in mortality due to breast cancer decreased from 1993 to 2007 and this trend continues at the present time. However, the mortality decreased in younger and middle-aged patients, but in older women remained unchanged [ 10 ].…”
Section: Introductionmentioning
confidence: 99%